2012
DOI: 10.1007/s10865-012-9460-y
|View full text |Cite
|
Sign up to set email alerts
|

Anger, adiposity, and glucose control in nondiabetic adults: findings from MIDUS II

Abstract: OBJECTIVE Anger has been linked to cardiovascular disease, but few studies have examined the relationship between anger and type 2 diabetes. The aim was to investigate associations among different indicators of anger expression, adiposity, and nondiabetic glucose metabolism in a national survey of adults. RESEARCH DESIGN AND METHODS Participants were 939 adults without diabetes in the Midlife in the US study (MIDUS II). Glucose metabolism was characterized by fasting glucose, insulin, insulin resistance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
2
6
1
Order By: Relevance
“…While previous studies by our research group and others [58] have shown that the combined influences of obesity and psychosocial variables are associated with higher glucose and HbA 1c , no relationships were detected for glucose or HbA 1c in the present study. The overall pattern of findings underscore the fact that these four clinical indicators of glucose regulation track different steps in the progression from normoglycemia to disease [25].…”
contrasting
confidence: 94%
See 2 more Smart Citations
“…While previous studies by our research group and others [58] have shown that the combined influences of obesity and psychosocial variables are associated with higher glucose and HbA 1c , no relationships were detected for glucose or HbA 1c in the present study. The overall pattern of findings underscore the fact that these four clinical indicators of glucose regulation track different steps in the progression from normoglycemia to disease [25].…”
contrasting
confidence: 94%
“…Our findings extend previous work showing that other psychosocial vulnerability factors such as stress-induced catecholamine release, perceived discrimination, anger expression, and work stress interact with BMI and central adiposity to predict different clinical indicators of glucose metabolism [58]. Taken together, these lines of inquiry suggest that overweight and obese people, who are already at a higher risk for disease due to increased production of free fatty acids and pro-inflammatory cytokines by adipose tissue [26], may be more susceptible to the effects of psychosocial vulnerabilities on clinical indicators of glucose metabolism.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Our findings are, for instance, in concordance with studies of the pathogenic impact of perseverative cognition, ruminations and worries 39. Correspondingly, low self-esteem,40 unfairness,41 lack of well-being,25 42 work dissatisfaction,43 loneliness,44 lack of social relationships,45 subjective social–evaluative threat46 and anger47 have been related to impaired health. A perceived lack of purpose in life has recently been connected to allostatic load,48 49 as has compromised sleep quality 50–52…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, both depression and anger have been shown to interact with obesity in diabetes. [61][62][63][64][65]…”
Section: Psychological Attitudes and Biomarkersmentioning
confidence: 99%